Gambaran Penyebab Stunting pada Balita 24-59 Bulan di Wilayah Kerja Puskesmas Susut 1 Bangli - Ayu Usha Vedaswari Widnyana; Made Dharmesti Wijaya; Luh Gede Pradnyawati (Aesculapius Medical Journal, 2022)
Abstract [Overview of the Stunting Determinants in 24-59 Months Toddlers in Puskesmas Susut 1 Bangli] Stunting is when a toddler has shorter height than the standard height for their age due to chronic malnutrition. Indonesia is ranked third for highest prevalence of stunting in Southeast Asia. Furthermore, Bangli is the regency with the second highest stunting prevalence in Bali Province, Indonesia (28,4%). Based on survey at Puskesmas Susut 1 Bangli, there are 66 toddlers with stunting in August 2020. Maternal, child, parenting, and family socio-economic are factors that could contribute to stunting. This study aims to describe the causes of stunting in toddlers aged 24-59 months in the working area of Puskesmas Susut 1 Bangli. A descriptive qualitative method was used with 10 main informants and 15 supporting informants. Primary data from in-depth interviews and observation, as well as secondary data from toddlers’ documents were obtained. The data were analyzed by interactive analysis and presented in narrative text. The results of this study indicate that the factors that may be associated with stunting incidence are maternal and parenting factors. The low education of mothers and insufficient diet given by the mothers or guardians seemed to be stunting determinants from maternal and parenting factors. Meanwhile, no abnormalities are found in the childs’ and family socio-economic factors. In conclusions, the factors that influence the stunting incidence in this study are low maternal education and insufficient diet.